Occurrence of Epistylis anastatica (Linnaeus, 1767) (Ciliophora: Peritrichia) on Mesocyclops isabellae Dussart & Fernando (Crustacea: Copepoda: Cyclopoida) in India, with an annotated checklist of species of Epistylis reported as Epibionts of Cyclopoid Copepods and resources for their identification - Clamp, John C.; Chatterjee, Tapas; Fernandez-Leborans, Gregorio (Zootaxa, 2016)
The colonial peritrich ciliate Epistylis anastatica (Linnaeus, 1767) was discovered living as an epibiont on Mesocyclops isabellae Dussart & Fernando, 1988 collected from a pond in Andhra Pradesh state, India. This is the first report of Epistylis on this host, and a description of its morphological characteristics is provided. The biomass of colonies of E. anastatica relative to that of their hosts was relatively high, being greater than that of the host in some cases (8.11 mm3 vs. 1.14 mm3 or less), and this epibiotic burden has the potential to have an impact on the host’s activities. Relationships between epibiotic peritrichs and microcrustaceans like cyclopoid copepods may be much more complex than previously supposed and merit more thorough investigation. Species of Epistylis are commonly found on cyclopoid copepods, but resources for taxonomic identification are limited and scattered; therefore, an annotated checklist of all species reported from cyclopoid copepods and a summary of the diagnostic characteristics of each one is provided as an aid to investigators. Some records of Epistylis spp. from cyclopoid copepods that are accompanied by documentary evidence are misidentifications, raising the suspicion that many other undocumented records also may be erroneous; therefore, it is suggested that authors provide supplementary descriptions and figures.